Kepemimpinan Perempuan dan Persepsi Masyarakat terhadap Kesetaraan Gender di Mandailing Natal - Nur Hibbah; Desi Safitri (Jurnal Kajian dan Penelitian Umum, 2024)
Women's leadership in the perspective of gender equality in Mandailing Natal, a region with strong traditional customs and religious values. This study aims to understand the community's perception of women's leadership and analyze the obstacles and opportunities faced by women in leadership. Using gender theory and transformational leadership theory, this study identifies that patriarchal cultural norms and conservative religious interpretations are the main challenges for women leaders. However, women's success in informal leadership contexts, such as social organizations, shows the potential to change community perceptions. This study contributes to the academic literature on women's leadership and offers strategic recommendations to promote gender equality at the local level. Furthermore, this study finds that education and exposure to gender equality issues can play an important role in transforming community attitudes. In addition, more inclusive policy support and gender mainstreaming at the local level are key to opening more space for women in formal leadership. This study offers practical and theoretical contributions in understanding the dynamics of women's leadership and provides strategic recommendations to realize gender equality in Mandailing Natal.